2012
DOI: 10.1111/j.1464-410x.2012.11465.x
|View full text |Cite
|
Sign up to set email alerts
|

Low pretreatment serum total testosterone is associated with a high incidence of Gleason score 8–10 disease in prostatectomy specimens: data from ethnic Chinese patients with localized prostate cancer

Abstract: Study Type – Prognosis (prospective cohort) Level of Evidence 2b What's known on the subject? and What does the study add? Previous data from clinically localized prostate cancer (PCa) series treated with radical prostatectomy (RP) have suggested that low preoperative serum total testosterone level is associated with more aggressive PCa; however, the definition of low preoperative total testosterone level varied among these studies (from 220 ng/dL to 387 ng/dL). Moreover, no relevant data exist in the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 29 publications
4
41
4
Order By: Relevance
“…The present study demonstrated that, compared with high levels of total serum testosterone at the time of diagnosis, low total serum testosterone levels at the time of diagnosis were associated with aggressive features of PCa, which is consistent with the results of previous studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). A previous pooled analysis of 18 prospective studies identified that pre-diagnosis serum testosterone levels were not associated with the high-risk form of PCa (32); however, the testosterone levels in this analysis were measured years prior to PCa diagnosis and a different definition of high-risk form of PCa was used.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present study demonstrated that, compared with high levels of total serum testosterone at the time of diagnosis, low total serum testosterone levels at the time of diagnosis were associated with aggressive features of PCa, which is consistent with the results of previous studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). A previous pooled analysis of 18 prospective studies identified that pre-diagnosis serum testosterone levels were not associated with the high-risk form of PCa (32); however, the testosterone levels in this analysis were measured years prior to PCa diagnosis and a different definition of high-risk form of PCa was used.…”
Section: Discussionsupporting
confidence: 82%
“…However, studies on the association between testosterone and PCa risk have produced conflicting results (8,9). Numerous studies have demonstrated that low, rather than high, testosterone levels at diagnosis were associated with various markers of poor prognosis, including an advanced pathological stage, higher Gleason scores, higher PSA levels, seminal vesicle invasion and positive surgical margins (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Few studies have further investigated whether low levels of testosterone predict poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…20 Park et al 9 demonstrated a correlation between hypogonadism and unfavorable outcomes in prostatic biopsies, such as increased incidence of GS ≥ 8. Several studies, despite adopting different thresholds for the definition of hypogonadism, have confirmed an association between low testosterone levels and adverse characteristics and outcomes for PCa, including higher Gleason score, 21,22 higher pathological stage 10,22 and increased risk for disease progression. 23 However, a number of investigations failed to show an association between low serum testosterone levels and high-risk characteristics of PCa specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Men with Gleason 8 or greater had significantly lower serum testosterone, 14.2 nmol/l (410 ng/dl) versus 11.1 nmol/l (320 ng/dl) (p = 0.028). Furthermore, hypogonadal men, with total morning testosterone <8.6 nmol/l (250 ng/dl), were more likely to have Gleason 8 or greater disease (p = 0.005) [Dai et al 2012].…”
Section: Endogenous Testosterone In Prca Patientsmentioning
confidence: 99%